An Implementation of Total Quality Management and Its Impact on The Performance of Food and Beverage Industry of Cameroon - Gome Tsamo, Natacha Fabiola (2014)
The prime notion of this project is to evaluate the implementation of Total Quality Management and its impact on organisational performance. The research is focused on the Food and Beverage Industry of Cameroon. In order to achieve the research goals and objective, primary and secondary data collection methods are used. The use of questionnaires and conducting interviews are essential as they assist in providing credible and valid data. Regression analysis is also used as it helped with the presentation and data analysis.